2019
DOI: 10.1038/s41559-019-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

The genetic history of admixture across inner Eurasia

Abstract: The indigenous populations of inner Eurasia, a huge geographic region covering the central Eurasian steppe and the northern Eurasian taiga and tundra, harbor tremendous diversity in their genes, cultures and languages. In this study, we report novel genome-wide data for 763 individuals from Armenia, Georgia, Kazakhstan, Moldova, Mongolia, Russia, Tajikistan, Ukraine, and Uzbekistan. We furthermore report additional damage-reduced genome-wide data of two previously published individuals from the Eneolithic Bota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 70 publications
11
136
0
4
Order By: Relevance
“…By the end of the Mongol period the genetic make-up of the Eastern Steppe had dramatically changed, retaining little of the ANE ancestry that had been a prominent feature during its prehistory. Today, ANE ancestry survives in appreciable amounts only in isolated Siberian groups and among the indigenous peoples of the Americas (Jeong et al, 2019). The genetic profile of the historic Mongols is still reflected among contemporary Mongolians, suggesting a relative stability of this gene pool over the last ∼700 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the end of the Mongol period the genetic make-up of the Eastern Steppe had dramatically changed, retaining little of the ANE ancestry that had been a prominent feature during its prehistory. Today, ANE ancestry survives in appreciable amounts only in isolated Siberian groups and among the indigenous peoples of the Americas (Jeong et al, 2019). The genetic profile of the historic Mongols is still reflected among contemporary Mongolians, suggesting a relative stability of this gene pool over the last ∼700 years.…”
Section: Discussionmentioning
confidence: 99%
“…To analyse our dataset in the context of known ancient and modern genetic diversity, we merged it with previous published modern genomic data from i) 225 worldwide populations genotyped on the Human Origins array (Jeong et al, 2019; Lazaridis et al, 2014), ii) 300 high-coverage genomes in the Simons Genome Diversity Project (“SGDP”) (Mallick et al, 2016), and currently available ancient genomic data across Eurasian continent (Allentoft et al, 2015; de Barros Damgaard et al, 2018; Damgaard et al, 2018; Fu et al, 2014, 2016; Haak et al, 2015; Haber et al, 2017; Harney et al, 2018; Jeong et al, 2016, 2018; Jones et al, 2015; Kilinç et al, 2016; Lazaridis et al, 2016, 2017; Mathieson et al, 2015, 2018; McColl et al, 2018; Narasimhan et al, 2019; Raghavan et al, 2014, 2015; Rasmussen et al, 2010, 2014, 2015; Sikora et al, 2019; Unterländer et al, 2017; Yang et al, 2017). We obtained 1,233,013 SNP sites (1,150,639 of which on autosomes) across our dataset when intersecting with the SGDP dataset, and 597,573 sites (593,124 of which on autosomes) when intersecting with the Human Origins array.…”
Section: Star Methods Textmentioning
confidence: 99%
“…We generated 94 direct AMS (Accelerator Mass Spectrometry) radiocarbon ( 14 C) dates as part of this study; 87 at Pennsylvania State University (PSU) and 7 at Poznan Radiocarbon Laboratory. The methods used at both laboratories are published, and here we summarize the methods from PSU.…”
Section: Methodsmentioning
confidence: 99%
“…Instead in the Late Bronze Age and Iron Age and afterward we have data from multiple Mongolian groups whose Yamnaya-related ancestry can only be modeled as deriving not from the initial Afanasievo migration but instead from a later eastward spread into Mongolia related to people of the Middle to Late Bronze Age Sintashta and Andronovo horizons who were themselves a mixture of ∼2/3 Yamnaya-related and 1/3 European farmer-related ancestry 5,7,8 . The Sintashta-related ancestry is detected in proportions of 5% to 57% in individuals from the Mongolia_LBA_6_Khovsgol (a culturally mixed group from the literature 14 ), Mongolia_LBA_3_MongunTaiga, Mongolia_LBA_5_CenterWest, Mongolia_EIA_4_Sagly, Mongolia_EIA_6_Pazyryk, and Mongolia_Mongol groups, with the most substantial proportions of Sintashta-related ancestry always coming from western Mongolia (Figure 3, Online Table 5). For all these groups, the qpAdm ancestry models pass when Afanasievo is included in the outgroups while models with Afanasievo treated as the source with Sintashta more distantly related outgroups are all rejected (Figure 3, Online Table 5).…”
mentioning
confidence: 99%
“…Hence, genetic and archeological evidence support a single/common origin of a population directly related to the maternal ancestors of some of the present-day Ket, Tofalar, Tuvan, Yakut, Buryat, as well as the Koryak individuals. It has been suggested that the Okunevo Culture derived ancestry from long-resident populations of the Altai-Sayan Upland whose roots may extend back to the Neolithic, if not before [35]. Supplementary Fig.…”
Section: Haplogroup A8mentioning
confidence: 99%